Effective Teaching Methods in Secondary School Art Education: Promoting Creativity and Critical Thinking - Aminova Sabina Anvar qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article examines effective teaching methods for secondary school art education that aim to enhance student creativity, engagement, and critical thinking. It focuses on interactive strategies, project-based learning, flipped classroom approaches, and the use of technology in the classroom. The study highlights how these methods can improve learning outcomes, foster personal growth, and support the development of both technical and conceptual artistic skills.